2008
DOI: 10.1038/nature07443
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Pten control neural and glioma stem/progenitor cell renewal and differentiation

Abstract: Glioblastoma (GBM) is a highly lethal brain tumor presenting as one of two subtypes with distinct clinical histories and molecular profiles. The primary GBM subtype presents acutely as high-grade disease that typically harbors EGFR, Pten and Ink4a/Arf mutations, and the secondary GBM subtype evolves from the slow progression of low-grade disease that classically possesses PDGF and p53 events1–3. Here, we show that concomitant CNS-specific deletion of p53 and Pten in the mouse CNS generates a penetrant acute-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
576
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(611 citation statements)
references
References 38 publications
29
576
3
3
Order By: Relevance
“…Conditional overexpression of c-Myc in mouse astroglia leads to brain tumors that resemble human malignant gliomas (Jensen et al, 2003). In addition, c-Myc prevents cell differentiation and promotes self-renewal of tumor cells derived from the pten/p53 double null mouse model (Zheng et al, 2008a). Taken together, these studies support an important role of c-Myc in GSC maintenance.…”
Section: Specific Transcription Factors and The Maintenance Of Glioblmentioning
confidence: 69%
See 1 more Smart Citation
“…Conditional overexpression of c-Myc in mouse astroglia leads to brain tumors that resemble human malignant gliomas (Jensen et al, 2003). In addition, c-Myc prevents cell differentiation and promotes self-renewal of tumor cells derived from the pten/p53 double null mouse model (Zheng et al, 2008a). Taken together, these studies support an important role of c-Myc in GSC maintenance.…”
Section: Specific Transcription Factors and The Maintenance Of Glioblmentioning
confidence: 69%
“…Recent studies demonstrated that inactivation of PTEN (a well-known tumor suppressor) promotes undifferentiated state of GSCs (Zheng et al, 2008a, b), suggesting PTEN may promote GSC differentiation. PTEN is a phosphatase with dual-specificity for both protein and lipid and is often mutated in GBMs (Fan et al, 2002;Zheng et al, 2008a). It has been well known that PTEN deletion or functional loss is linked to progression and/or immunoresistance of malignant gliomas (Parsa et al, 2007).…”
Section: Differentiation Of Glioblastoma Stem Cellsmentioning
confidence: 99%
“…Conditional knockout of Pten in neural stem cells revealed that Pten is indispensable for proper control of neural stem cell proliferation and self-renewal in the developing brain (Groszer et al, 2001). Double knockout of p53 and Pten led to compromised differentiation potential and sustained self-renewal of neural stem cells by means of elevated Myc expression (Zheng et al, 2008). Moreover, conditional deletion of Pten in a subpopulation of adult neural stem cells in the subventricular zone resulted in enhanced neural stem cell self-renewal.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Despite recent insights into molecular pathways involved in GBM pathogenesis, gained through comprehensive genetic analysis during the pilot project of 'The Cancer Genome Atlas' initiative (The Cancer Genome Atlas Research Network, 2008) and other studies (Furnari et al, 2007;Zheng et al, 2008), better understanding of the molecular basis and biology of gliomas is needed to validate the emerging, and design new, targeted therapies. Rampant genomic instability and resistance to genotoxic treatment modalities including ionizing radiation and chemotherapy are among the hallmarks of GBM (Furnari et al, 2007), implicating the cellular DNA damage response (DDR) machinery (Jackson and Luo et al, 2009) as an important factor in both pathogenesis and treatment response.…”
Section: Introductionmentioning
confidence: 99%